Hand carriage of aerobic Gram-negative rods by health care personnel - Adams, Brian G. (1982)
A quantitative culture technique (hand washed in a glove containing broth for 30 s) was used to determine the frequency of hand carriage of aerobic Gram-negative rods by various groups of health care workers and 104 control subjects. Overall, 31% of health care workers carried aerobic Gram-negative rods on their hands compared to 59% of control subjects (P < 0·001). Enterobacter agglomerans accounted for 40% of the isolates, and other Enterobacter spp. 7%. Other organisms included Acinetobacter calcoaceticus 21%, Serratia spp. 11%, Klebsiella spp. 10%, Moraxella spp. 3%, Pseudomonas spp. 3%, Proteus spp. 1·5%, Escherichia coli 1%; Morganella morganii, Citrobacter freundii, Aeromonas sp. and an isolate that was not speciated accounted for 0·5% each. We conclude that endemic hand carriage of aerobic Gram-negative rods by health care personnel is common, but significantly less than that of control subjects. Enterobacter agglomerans is found so frequently on the hands of control subjects that it must be considered part of the normal hand flora.